2019
DOI: 10.22161/ijeab.46.5
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Indigenous Rhizospheric Cyanobacteria as Potential Growth Promotor and Biocontrol of Ralstonia syzygii subsp. indonesiensis on Chili

Abstract: The use of microbial inoculants as biofertilizers and/or antagonists of phytopathogens provides a promising alternative to chemical fertilizers and pesticides. Cyanobacteria are a remarkable group of prokaryotes, which are known to exist independently and in symbiotic/facultative associations with a diverse range of members of the plant. Cyanobacteria inoculation had been reported to enhance the growth, nitrogen fixation and yields. Although, their establishment and role in plant growth promotion and biocontro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Additionally, Anabaena flos-aquae can completely suppress Ralstonia solanacearum, which causes brown rot disease in potatoes due to the production of antibiosis that is released into the environment [98]. Yanti et al [99] found that cyanobacteria were able to stop Ralstonia syzygii subsp. indonesiensis, which is the cause of many vascular diseases in different crops.…”
Section: The Role Of Cyanobacteria In Controlling Phytopathogensmentioning
confidence: 99%
“…Additionally, Anabaena flos-aquae can completely suppress Ralstonia solanacearum, which causes brown rot disease in potatoes due to the production of antibiosis that is released into the environment [98]. Yanti et al [99] found that cyanobacteria were able to stop Ralstonia syzygii subsp. indonesiensis, which is the cause of many vascular diseases in different crops.…”
Section: The Role Of Cyanobacteria In Controlling Phytopathogensmentioning
confidence: 99%
“…One currently developed biological agent for controlling plant pathogens is from the Plant Growth Promoting Rhizobacteria (PGPR) group [8]. One of the biological agents classified as PGPR is Bacillus spp.…”
Section: Introductionmentioning
confidence: 99%